2018
DOI: 10.2478/aoas-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing system and feeding intensity on the fattening performance and slaughter value of young crossbred bulls

Abstract: the aim of this study was to determine the effects of rearing system and feeding intensity on the fattening performance and slaughter value of 38 young crossbred bull calves. the calves were raised naturally with nurse cows (nc) or were fed milk replacer (mf) until 150 days of age. during the rearing period the nc calves were healthier and had higher average daily gain (by 0.15 kg) compared to the mf calves. after a 30-day transition period, the animals were fattened in intensive (i) and semi-intensive (si) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
5
8
0
Order By: Relevance
“…Conformation may vary depending on the physiological status, genotype and feeding style of animals. Nogalski et al (2018) determined, similar with our results, the value of the carcass conformation for milk feeder and nurse cow groups as medium (7 nearly). It did not observe any difference between in the conformation scores of the postweaning and finishing periods in Nuella cattle (Cancian et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Conformation may vary depending on the physiological status, genotype and feeding style of animals. Nogalski et al (2018) determined, similar with our results, the value of the carcass conformation for milk feeder and nurse cow groups as medium (7 nearly). It did not observe any difference between in the conformation scores of the postweaning and finishing periods in Nuella cattle (Cancian et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…A slightly lower Warner–Blatzer shear force values than those in our study, were reported by Bureš and Barton [47] for Fleckvieh bulls (49.8 N) and for Simmental bulls (48.19 N) [48]. Beef from cattle with a high intramuscular fat level often has a lower shear force [49], which is in accordance with results from our study. The color sensory attribute of the meat samples did not differ significantly between the cattle groups ( p > 0.05).…”
Section: Resultssupporting
confidence: 92%
“…This prolonging fattening period increases the animals age at slaughter, which may result in deterioration of the sensory quality of beef, i.e., its tenderness [ 9 ]. When grazing bulls, better results are obtained by using intensive feeding [ 10 ]. Bull calves reach slaughter maturity early and achieve optimal final body weight, and thus burden the environment to a lesser extent [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments conducted in our research team focus on the combined impact of the rearing system and intensity of feeding on the growth rates, carcass value, and meat quality from young bulls. Results regarding the growth rates of Polish Holstein–Friesian × Hereford calves, fattening performance and carcass characteristics were described in detail by Nogalski et al [ 10 ]. It was concluded that a suckling system with nurse cows is more beneficial than using a milk replacer distributed from automated stations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation